Pemberdayaan Masyarakat Melalui Diversifikasi Produk Olahan pada Kelompok Wanita Tani Sri Rejeki Banjarbaru Kalimantan Selatan: Community Empowerment Through Diversification of Processed Products in the Sri Rejeki Banjarbaru Women Farming Group South Kalimantan - Muthia, Rahmi; Akbar, Depy Oktapian; Putri, Aristha Novyra; Dewi, Citra Kharisma; Amalia, Elfa Annisa; Ananda, Lutfhia Rizky; Alfina, Sophia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The Sri Rejeki Women's Farmers Group (KWT) is in Landasan Ulin Utara District, Banjarbaru City—the majority of residents in the area work as farmers. The natural potential in the area supports agricultural activities such as the cultivation of Butterfly Pea flowers and Bawang Dayak. Several products from KWT Sri Rejeki have been marketed but could be more optimal and are still sold offline. Based on these things, it is necessary to carry out several activities, namely diversifying processed products, making new packaging, and expanding marketing activities. This activity aims to increase understanding regarding types of processed products, improve packaging, and increase capabilities at the product marketing stage. Methods include training on the diversification of processed products, product creation and assistance, packaging planning, online marketing, and evaluation. The products produced are simplicia, tea bags, and powder from Butterfly Pea flowers and Bawang Dayak bulbs. Online marketing is carried out via Instagram, Shopee, and Tokopedia with the account name kwtsrirejeki.